THE OCCURRENCE OF NON-PARASITIC MITES, Scheloribates sp. (ACARI: ORIBATIDA) ON ANURANS FROM URBAN AREAS IN SARAWAK - Ahmad Shahmi, Abdul Salim; Zalifah Husna, Ali; Abang Haziq, Abang Ismail; Madinah, Adrus (Faculty of Science and Technology (FST), Unversiti Kebangsaan Malaysia (UKM), 2023)
A survey of ectoparasitic infestation on anurans in urban areas of Kota Samarahan, Sarawak, Malaysian Borneo has been conducted from September 2019 until January 2020. This study aimed to determine the species prevalence and composition of ectoparasites on anuran in the urban area of Kota Samarahan. The host collection was done by using the method of Visual Encounter Survey (VES) and the hand-netting method. A total of 120 individuals comprising six anuran species namely, Chalcorana raniceps, Duttaphrynus melanostictus, Fejervarya limnocharis, Hoplobatrachus rugulosus, Kaloula pulchra and Polypedates leucomystax were captured and screened for ectoparasites. One species of non-parasitic Oribatida mites, Scheloribates species was found infested by four individuals (3.3%) of D. melanostictus. This preliminary survey produced the first record of non-parasitic mites found on anurans in the urban area of Kota Samarahan and further research needs to be done since the status of Scheloribates sp. is still unknown as the parasitic of anurans, and the finding can become a pioneer for future research.